2018
DOI: 10.15835/nsb10310222
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oil Composition and Antimicrobial Activity of Achillea biebersteinii Afan. (Asteraceae) from Erzincan Region, Turkey

Abstract: In the present study, chemical composition determination and in vitro antimicrobial effects of essential oil of Achillea biebersteinii plant grown under Erzincan ecological conditions were evaluated. Extractions were carried out with Clevenger apparatus and essential oil composition was determined by Gas Chromatography-Mass Spectrometry (GC-MS). Microorganisms used for the antimicrobial studies were Salmonella enterica serovar typhimirium ATCC 14028, Staphylococcus aureus subsp. aureus ATCC 25923, Yersinia pse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Among these studies, only one investigation showed the main compounds in the oil as p -cymene and ascaridole, without camphor and 1,8-cineole [ 47 ]. On the other hand, Sevindik et al (2018) studied the essential oil from the aerial parts of A. biebersteinii and demonstrated different major groups: 1,8-cineole (20.36%) and cyclohexanone (8.39%), followed by 2-cyclohexen-1-one (5.38%) and spathulenol (4.2%) [ 48 ]. In the literature, the variety of compounds and their concentrations are attributed to the different ecological regions of this plant as well as to the existence of different chemotypes of the species [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these studies, only one investigation showed the main compounds in the oil as p -cymene and ascaridole, without camphor and 1,8-cineole [ 47 ]. On the other hand, Sevindik et al (2018) studied the essential oil from the aerial parts of A. biebersteinii and demonstrated different major groups: 1,8-cineole (20.36%) and cyclohexanone (8.39%), followed by 2-cyclohexen-1-one (5.38%) and spathulenol (4.2%) [ 48 ]. In the literature, the variety of compounds and their concentrations are attributed to the different ecological regions of this plant as well as to the existence of different chemotypes of the species [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, several different types of Candida yeast were used to screen the antifungal activities of the samples in the present study. Many articles have demonstrated that several extracts and essential oils of Achillea species have shown promising antifungal effects despite their poor antibacterial activity [ 48 , 49 , 50 , 53 ]. Hence, the antimicrobial effects of Achillea species and their metabolites should be deeply investigated to reveal the responsible components of the activity.…”
Section: Resultsmentioning
confidence: 99%
“…The identified components of the essential oils, their percentages and retention indices are given in Table 1. found in thyme can be as low as 3% to as high as 60% of the total essential oils in thyme [16].…”
Section: Chemical Composition Of the Essential Oil Of Achillea Biebersteiniimentioning
confidence: 93%
“…Chrysanthemum species belongs to family Asteraceae (Liu et al, 2012). The Asteraceae family consists of approximately 23000 species and 1535 genera (Ozturk & Çetin, 2013;Sevindik et al, 2018). It has been reported that a large number of species of the Asteraceae family show pharmacological activities.…”
Section: Public Interest Statementmentioning
confidence: 99%
“…It has been reported that a large number of species of the Asteraceae family show pharmacological activities. The plants in this family include sesquiterpene lactone metabolites having biological activities such as antibacterial, antifungal, and antitumor, in addition to diterpenes and flavonoids (Sevindik et al, 2018). Indeed, it has the second rank after roses in the economic perspective and in production.…”
Section: Public Interest Statementmentioning
confidence: 99%